MEDU-21. LOSS OF THE TRANSCRIPTIONAL CO-REPRESSOR BCOR LEADS TO OVEREXPRESSION OF THE GROWTH FACTOR IGF2 AND SHH MEDULLOBLASTOMA TUMOR FORMATION. (23rd April 2019) - Kutscher, Lena; Batora, Nadja; Okonechnikov, Konstantin; Clark, Jessica; Vouri, Mikaella; Rijn, Sjoerd van; Gearhart, Micah; Orr, Brent; Korshunov, Andrey; Kool, Marcel; Bardwell, Vivian; Pfister, Stefan M; et al.
Abstract: Sonic hedgehog (SHH) medulloblastoma (MBSHH ) accounts for approximately 25% of all MB diagnoses and is the predominant disease subgroup in infants and adults. Pediatric MBSHH is caused by an abnormal activation of the SHH pathway in granule cell progenitors (GNPs) in the developing cerebellum, but also requires additional secondary lesions. These secondary genetic hits often occur in chromatin modifying genes, but functional evidence for a role of these mutations in MBSHH progression is lacking. We have identified the transcriptional co-repressor BCOR, a subunit of the PRC1.1 complex, as recurrently mutated in approximately 10% of MBSHH patients and likely to function as a suppressor of MBSHH tumor formation. Conditional genetic ablation of Bcor in GNPs strongly accelerated tumor formation in Ptch1 +/ - mice in a cell-autonomous manner. Moreover, we found that the growth factor Igf2 is 100-fold upregulated in Bcor -deficient Ptch1 +/- MBs compared to control tumors. This upregulation was observed in neoplastic lesions but not in normally differentiating GNPs, suggesting potential epigenetic regulation of Igf2 by Bcor during tumorigenesis. Overexpression of Igf2 in Ptch1 +/- GNPs was sufficient to generate tumors with 100% penetrance. Intriguingly, in a small subset of human MBSHH, we observed an association between deleterious BCOR mutations and high IGF2 expression. Our data suggest that loss of Bcor cooperates with aberrant SHH signaling to promote Igf2-dependent tumor growth.